2010
DOI: 10.1371/journal.pone.0011315
|View full text |Cite
|
Sign up to set email alerts
|

Can Preening Contribute to Influenza A Virus Infection in Wild Waterbirds?

Abstract: Wild aquatic birds in the Orders Anseriformes and Charadriiformes are the main reservoir hosts perpetuating the genetic pool of all influenza A viruses, including pandemic viruses. High viral loads in feces of infected birds permit a fecal-oral route of transmission. Numerous studies have reported the isolation of avian influenza viruses (AIVs) from surface water at aquatic bird habitats. These isolations indicate aquatic environments have an important role in the transmission of AIV among wild aquatic birds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 50 publications
3
55
0
3
Order By: Relevance
“…The prevalence rate of Orthomyxovirus we calculated (4.3%) in mallard is consistent with that reported for the Mediterranean area (Delogu et al, 2011). In our study, the inverse multiple sample census seems to have been a reliable method since it yielded an estimate very close to the crude sample prevalence, suggesting that, for this purpose, the method could be of great utility.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence rate of Orthomyxovirus we calculated (4.3%) in mallard is consistent with that reported for the Mediterranean area (Delogu et al, 2011). In our study, the inverse multiple sample census seems to have been a reliable method since it yielded an estimate very close to the crude sample prevalence, suggesting that, for this purpose, the method could be of great utility.…”
Section: Discussionsupporting
confidence: 91%
“…Also, a recent study has advanced the hypothesis that the preen oil which aquatic birds use to waterproof their feathers with a lipidic film could attract AIVs from contaminated water, thus acting as a sort of a natural mechanism of virus concentration and a source of infection via preening activity (Delogu et al 2011). The study also suggested that a preened body could be the common denominator explaining the occurrence of AIV infection in different taxonomic groups of aquatic avifauna.…”
Section: Introductionmentioning
confidence: 91%
“…Bird feces are also a source of antibiotic resistance genes (34,39,50). Recently, because of avian influenza, concerns have risen about pathogen movement due to bird migration (8,10,17,28,30).Although pathogens occur in bird feces, exposure to bird feces is considered less harmful to humans than exposure to other sources of fecal contaminants, especially that of humans (43, 51). For example, molecular evidence indicates that genotypes of certain parasites in birds, such as Giardia and Cryptosporidium, are host adapted and cannot cross-infect among different hosts (20, 57).…”
mentioning
confidence: 99%
“…Bird feces are also a source of antibiotic resistance genes (34,39,50). Recently, because of avian influenza, concerns have risen about pathogen movement due to bird migration (8,10,17,28,30).…”
mentioning
confidence: 99%
“…Foram conduzidas seis expedições científicas a três localidades no estado do Pará: i) , 1988;WEBSTER et al, 1992;FOUCHIER et al, 2007;WEBSTER et al, 2007;SALOMON;WEBSTER, 2009;FEREIDOUNI et al, 2010;HANSBRO et al, 2010;DAOUST et al, 2011;GAIDET et al, 2012;BROWN et al, 2013 É sabido que os subtipos de AIV podem exibir tropismos teciduais distintos e serem preferencialmente excretados pela via respiratória ou digestiva (FEREIDOUNI et al, 2010;HOYE et al, 2010;PARMLEY et al, 2011;ZOWALATY et al, 2011; SPACKMAN et al, 2002;KRAUSS et al, 2004;FOORD et al, 2009;FAIX et al, 2009;DELOGU et al, 2010;GILBERT et al, 2012;GONZÁLEZ-REICHE et al, 2012;HILL et al, 2012;GERLOFF et al, 2013).…”
Section: Expedições Científicasunclassified